OPTIMALISASI BANTUAN OPERASIONAL KELUARGA BERENCANA UNTUK MENINGKATKAN AKSES DAN KUALITAS PELAYANAN KELUARGA BERENCANA DI WILAYAH KEPULAUAN MALUKU - Rohani, Siti (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Maluku Province faces great challenges in improving access to and quality of family planning services, especially for the Long-Term Contraceptive Method. With a low MHJP participation rate of 18.2% compared to the national average of 23.9%, and an unmet need of 19.21%, it is clear that there are still gaps in family planning services. Although the realization of the Family Planning Operational Assistance budget has reached 94.27%, its utilization has not been optimal in increasing the coverage and quality of family planning services. This is due to weaknesses in planning, monitoring, flexibility in the use of funds, and coordination between stakeholders. Optimizing the management of BOKB must be a priority to increase the effectiveness of the family planning program in Maluku. Regulation-based policies supported by the theory of Good Governance in Public Finance and Policy Implementation are approaches that can ensure transparency, accountability, and effectiveness in the management of BOKB funds. For this reason, the most recommended policy is BOKB planning based on data and field needs and increased transparency and accountability in fund management. The implementation of this policy is expected to increase the coverage of MHJP family planning services, especially in remote areas and islands, in order to reduce the unmet need rate and expand access to services for the community.